1996
DOI: 10.1523/jneurosci.16-19-06307.1996
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Synapses

Abstract: The strength of many synapses is modified by various use and time-dependent processes, including facilitation and depression. A general description of synaptic transfer characteristics must account for the history-dependence of synaptic efficacy and should be able to predict the postsynaptic response to any temporal pattern of presynaptic activity. To generate such a description, we use an approach similar to the decoding method used to reconstruct a sensory input from a neuronal firing pattern. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 19 publications
2
62
2
Order By: Relevance
“…7D), suggesting an additional faster depression (Dobrunz et al, 1997;Varela et al, 1997), or that factors in addition to depletion may be contributing to depression (Zucker and Regehr, 2002). A third approach that will be important to quantify dynamic changes in the components is modeling of the release process Sen et al, 1996;Varela et al, 1997;Dittman et al, 2000;Matveev et al, 2002;Aristizabal and Glavinovic, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…7D), suggesting an additional faster depression (Dobrunz et al, 1997;Varela et al, 1997), or that factors in addition to depletion may be contributing to depression (Zucker and Regehr, 2002). A third approach that will be important to quantify dynamic changes in the components is modeling of the release process Sen et al, 1996;Varela et al, 1997;Dittman et al, 2000;Matveev et al, 2002;Aristizabal and Glavinovic, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that presynaptic depression at the CF synaptic connection may be acting as a low-pass filter. Recent modelling studies indicate that temporal changes in release probability can shape the frequency-dependent transmission properties at central connections (Sen et al 1996;Tsodyks & Markram, 1997). The unusual temporal characteristics of release probability at the CF terminal may therefore have an important influence on output coding of the cerebellum.…”
Section: Quantal Sizementioning
confidence: 99%
“…Understanding this dynamic behaviour is central to understanding transmission, since synaptic efficacy, at any given time, is dependent on the recent history of the input. Furthermore, modelling studies have shown that the temporal behaviour of synaptic efficacy (the tendency to exhibit short-term facilitation or depression) is important in determining the pattern of frequency-coded information that is transmitted to the postsynaptic cell (Sen, Jorge-Rivera, Marder & Abbott, 1996;Tsodyks & Markram, 1997). Since the early work of del Castillo & Katz (1954b) at the NMJ, synaptic depression is generally assumed to have a presynaptic locus.…”
mentioning
confidence: 99%
“…Estimating the replenishment rate is difficult. In previous studies the assumption was made that the pool sizes are constant (Wu and Betz 1998) and that the replenishment rate remains constant with stimulation (Dittman and Regehr 1998;Sen et al 1996), but the validity of these assumptions is problematic.…”
Section: Introductionmentioning
confidence: 99%